Doing more with less: The catalytic function of IMF lending and the role of program size - Tobias Krahnke (Deutsche Bundesbank, 2020)
Financial assistance provided by the International Monetary Fund (IMF) is supposed to unlock other financing, acting as a catalyst for private capital flows. The empirical evidence of the presence of such a catalytic effect has, however, been mixed. This paper shows that a possible explanation for the rather inconclusive empirical evidence to date is the neglect of the size of an IMF program. Applying a novel identification strategy to account for endogenous selection into (large) adjustment programs, and using a comprehensive data set spanning the years 1990-2018, we show that the catalytic effect of IMF financial assistance is weakened - and potentially reversed - if the size of a program exceeds a certain level. We argue that large IMF financial assistance coupled with the IMF's preferred creditor status can lead to a crowding-out of private investors by increasing their loss in the event of default. Our findings add to the debate on the optimal size of Fund-supported programs and can also inform the broader policy discussions on the adequacy of IMF resources.
Keywords: F32; F33; F36; G01; G15; 330; International Monetary Fund; catalysis; capital flows; financial crises